Prevalencia y factores asociados al trauma cráneo encefálico en pacientes ingresados en el servicio de emergencia del Hospital del IESS - Portoviejo de febrero a julio del 2015. - Calle Piedra, Jimmy Daniel (2015)
Objective: To determine the prevalence of head trauma and its associated factors among patients admitted to the Emergency Hospital IESS Portoviejo through surveys in order to meet the specific entities that cause this disease and lead to treatment.\nMaterials and Methods: An observational descriptive quantitative study type of cross section, which is used as an information tool form data collection which after validation will consist of: variables as will be socio-demographic, etiology, associated factors head trauma.\nResults: In this study we found that the prevalence of traumatic brain injury in the IESS-Portoviejo is 45.8% compared with 54.2% who suffered injuries to any other form.\nConclusions: In patients with traumatic brain injury the risk factors that had the greatest influence were: falls (39.5%), followed by traffic accidents (31.6%), this directly associated with drug use (52.6%), including alcohol as the primary drug (47.4%), mainly affecting people who were in the age of young adults (26.3%) with precarious (81.6%) income of males (68.4%) with level of education of any kind (36.8 ).